Complementary treatment of allergic rhinoconjunctivitis: the role of the nutraceutical Lertal(R) - Marseglia, Gianluigi; Licari, Amelia; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Nutraceuticals represent interesting therapeutic options in clinical practice. In this regard, a new compound has been designed: Lertal®. It contains quercetin, perilla extract, and vitamin D3. These agents exert anti-allergic and anti-inflammatory activities. This article reports and discusses the results of four clinical studies conducted in adult and paediatric patients suffering from AR. Outcomes provided evidence that Lertal® may significantly prevent clinical worsening when prescribed as add-on to continuous antihistaminic treatment and also prevent clinical exacerbations, such as the need of rescue medication, when used alone as preventive strategy in AR patients.